Description of Mothers' Knowledge about Exclusive Breastfeeding - Aurellia Santya Marthatia; Sulastri Sulastri (Indonesian Journal of Global Health Research, 2025)
Exclusive breastfeeding is very important for infant health, but its coverage in Indonesia is still low. One of the causes is the lack of knowledge of mothers about the importance of exclusive breastfeeding. This study aims to describe the level of knowledge of mothers about exclusive breastfeeding in the Kartasura Health Center Working Area and analyze the factors that influence it. This method uses a quantitative descriptive research design with a cross-sectional approach. The sample consisted of 51 mothers with babies aged 0-24 months, selected using a purposive sampling technique. Data were collected through a questionnaire that had been tested for validity and reliability, then analyzed univariately. The results showed that 51% of respondents had sufficient knowledge, 31.4% low, and 17.6% good. Contributing factors include age, education, occupation, number of children, and age of the last child. Higher education is associated with better knowledge. This conclusion shows that there are still many mothers with low levels of knowledge about exclusive breastfeeding, so more intensive health education and interventions are needed. Socialization and counseling by health workers are expected to increase the success of exclusive breastfeeding.